Arterial aneurysm localization is sex-dependent - Körfer, Daniel; Grond-Ginsbach, Caspar; Hakimi, Maani; Böckler, Dittmar; Erhart, Philipp (Journal of Clinical Medicine, 2022)
The aim of this study was to investigate sex-dependent aneurysm distributions. A total of 3107 patients with arterial aneurysms were diagnosed from 2006 to 2016. Patients with anything other than true aneurysms, hereditary connective tissue disorders or vasculitides (n = 918) were excluded. Affected arterial sites and age at first aneurysm diagnosis were compared between women and men by an unpaired two-tailed t-test and Fisher’s exact test. The study sample consisted of 2189 patients, of whom 1873 were men (85.6%) and 316 women (14.4%) (ratio m:w = 5.9:1). Men had considerably more aneurysms in the abdominal aorta (83.4% vs. 71.1%; p < 0.001), common iliac artery (28.7% vs. 8.9%; p < 0.001), internal iliac artery (6.6% vs. 1.3%; p < 0.001) and popliteal artery (11.1% vs. 2.5%; p < 0.001). In contrast, women had a higher proportion of aneurysms in the ascending aorta (4.4% vs. 10.8%; p < 0.001), descending aorta (11.1% vs. 36.4%; p < 0.001), splenic artery (0.9% vs. 5.1%; p < 0.001) and renal artery (0.8% vs. 6.0%; p < 0.001). Age at disease onset and further aneurysm distribution showed no considerable difference. The infrarenal segment might be considered a natural border for aneurysm formation in men and women suspected to have distinct genetic, pathophysiologic and ontogenetic factors. Screening modalities for women at risk might need further adjustment, particularly thoracic cross-sectional imaging complementation.
Gesehen am